Prenatal and Postnatal Cardiac Development in Offspring of Hypertensive Pregnancies - Christina Y. L. Aye; Adam J. Lewandowski; Pablo Lamata; Ross Upton; Esther Davis; Eric O. Ohuma; Yvonne Kenworthy; Henry Boardman; Annabelle L. Frost; Satish Adwani; Kenny McCormick; Paul Leeson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Pregnancy complications such as preterm birth and fetal growth restriction are associated with altered prenatal and postnatal cardiac development. We studied whether there were changes related specifically to pregnancy hypertension. Methods and Results Left and right ventricular volumes, mass, and function were assessed at birth and 3 months of age by echocardiography in 134 term‐born infants. Fifty‐four had been born to mothers who had normotensive pregnancy and 80 had a diagnosis of preeclampsia or pregnancy‐induced hypertension. Differences between groups were interpreted, taking into account severity of pregnancy disorder, sex, body size, and blood pressure. Left and right ventricular mass indexed to body surface area (LVMI and RVMI) were similar in both groups at birth (LVMI 20.9±3.7 versus 20.6±4.0 g/m2, P=0.64, RVMI 17.5±3.7 versus 18.1±4.7 g/m2, P=0.57). However, right ventricular end diastolic volume index was significantly smaller in those born to hypertensive pregnancy (16.8±5.3 versus 12.7±4.7 mL/m2, P=0.001), persisting at 3 months of age (16.4±3.2 versus 14.4±4.8 mL/m2, P=0.04). By 3 months of age these infants also had significantly greater LVMI and RVMI (LVMI 24.9±4.6 versus 26.8±4.9 g/m2, P=0.04; RVMI 17.1±4.2 versus 21.1±3.9 g/m2, P<0.001). Differences in RVMI and right ventricular end diastolic volume index at 3 months, but not left ventricular measures, correlated with severity of the hypertensive disorder. No differences in systolic or diastolic function were evident. Conclusions Infants born at term to a hypertensive pregnancy have evidence of both prenatal and postnatal differences in cardiac development, with right ventricular changes proportional to the severity of the pregnancy disorder. Whether differences persist long term as well as their underlying cause and relationship to increased cardiovascular risk requires further study.